The Influence of Leadership Style and Stakeholders on Sustainable Village Development Through Community-Based Tourism - Habibie, Fachrul Husain; Nurbaeti, Nurbaeti; Mariati, Sri; Mustika, Amalia (Integrated Journal of Business and Economics (IJBE), 2025)
This research aims to analyze the influence of leadership style and stakeholders on community-based tourism and its impact on sustainable village development. Quantitative research was carried out by distributing questionnaires. The research method used is path analysis. The research location is in the Borobudur Tourism Village area. The objects of this research are community groups, business actors and local governments. The population in this study was 9,826 people. Meanwhile, the sample based on the Slovin formula was 385 people. Research findings show that a transactional leadership style focusing on supervision and direction increases community involvement in developing tourist villages. In addition, although stakeholders do not directly influence CBT, they still play an essential role in supporting infrastructure development and improving community skills through CSR funds. The development of sustainable tourism villages is more influenced by community collaboration, understanding of sustainability principles, and diversification of tourism products other than culinary. This research implies the need for tourism village managers to increase community involvement in every stage of development, diversify tourism products, and strengthen collaboration between government, the private sector and the community. Then, the use of technology and social media can expand market reach. At the same time, the community must play an active role in preserving culture and the environment to support the sustainability of tourist villages.